A new approach to Y3Al5O12 transparent ceramics by vacuum sintering of spray-dried xerogels. Issue 1 (January 2016) - Balabanov, S.S.; Gavrishchuk, E.M.; Drobotenko, V.V.; Palashov, O.V.; Rostokina, E.Ye.; Yavetskiy, R.P.
Abstract: We report fabrication of Y3 Al5 O12 optical ceramics via compaction of amorphous xerogel obtained by spray-drying of 5AlOOH(NO3 )0.07 ·3Y(OH)2 (CH3 COO) aggregation-resistant sol, calcination to convert it into garnet phase and subsequent vacuum sintering. The spray drying conditions of the hydrosol have been optimized to ensure formation of spherical granules of xerogel with average diameter of about 330 nm. The thermal decomposition of amorphous precursor and its conversion to pure garnet phase have been studied by DSC, TG and XRD methods. Pressing of the xerogel allows one to achieve quite uniform microstructure of green bodies with well-developed net channels of pores which is beneficial for achieving high sinterability. Transparent Y3 Al5 O12 ceramics possessing the in-line transmission of about 80% at λ =1064 nm and the residual porosity of ∼5×10 −3  vol% have been obtained by vacuum sintering of the amorphous xerogels with the green density of 26%.